COMPARISON OF THERMAL RESISTANCE AND HUMIDITY MODE EXTERNAL WALLS OF RESIDENTIAL BUILDINGS BEFORE AND AFTER HER INSULATION - , Л. В., А. В. (Municipal economy of cities (Technical science), 2013)
This paper gives a calculation of temperature distribution along the fibers for the construction of the wall before and after the insulation and water vapor built diagrama which clearly shows the shift of the condensation zone in the last layers of fencing, which allows for a considerable period, to preserve the basic design of the house.